Micro-morphological and molecular characteristics of Jasminum binhchauense - Van, Hong Thien; Nguyen-Thi, Minh Thu; Le, Hong Thia; Le-Thi, Thu Trang; Nguyen-Phi, Nga (Journal of Phytology, 2025)
Jasminum binhchauense was recently described as a new species to science of which its specimen was found in Binh Chau-Phuoc Buu Nature Reserve, Vietnam. This study aims to characterize the DNA barcode and micro-morphological traits of J. binhchauense for the first time. As a result, the anatomical characteristics of the studied species were similar to those of J. azoricum. In addition, the matK, psaB, and psbB regions of J. binhchauense were successfully amplified and sequenced and they were also deposited at the NCBI database with the accession numbers of PQ415075, PQ415076, and PQ415077, respectively. The pairwise alignment of the matK, psaB, and psbB regions between J. binhchauense and J. nervosum, a morphologically resembled species, provided five, one, and two non-homologous locations, respectively.